CASE STUDY: INTERVENSI FISIOTERAPI PADA KASUS CARPAL TUNNEL SYNDROMEE (CTS) DENGAN MODALITAS ULTRASOUND (US) DAN CARPAL BONE MOBILIZATION UNTUK MENGEMBALIKAN AKTIVITAS FUNGSIONAL TANGAN - Ayu Permata; Perigel Saifullah Putra Syam (LPPM Universitas Abdurrab, 2024)
Background: Carpal Tunnel Syndromee (CTS) is an entrapment neuropathy that most often occurs in the wrist. This syndromee occurs due to pressure on the median nerve as it passes through the carpal tunnel in the wrist, precisely under the flexor retinaculum. The problems that occur in this case are pain in the wrist, pinching of the median nerve, decreased functional ability of the hand. Objective: This research is aimed at Carpal Tunnel Syndromee sufferers to improve the functional abilities of the hands. Research Method: Case study with 1 sample person suffering from Carpal Tunnel Syndromee with Severe Disability. Ultrasound intervention and carpal bone mobilization 3 times a week for 3 weeks. This research was conducted at the Tampan Pekanbaru Psychiatric Hospital in April-May 2022. The instrument used to measure hand functional ability was the Wrist Hand Dissability Index (WHDI. The pre and post test research design was to compare WHDI scores. Results: The results obtained were an increase in the functional ability of the hand, namely from a score = 24/50 x 100% = 48% (Severe Disability/severe disability) to a Score: 16/50 x 100% = 32% (Moderate). Conclusion: Ultrasound intervention and mobilization of the carpal bones are conservative interventions in the treatment of Carpal Tunnel Syndromee which can restore the functional ability of the hand.